ROLE OF AGRICULTURAL MACHINE TOOLS IN THE IMPROVEMENT OF RICE PRODUCTION IN CENTRAL OF JAVA - Wahyuningsih, Sri (Prosiding Seminar Nasional Sains Dan Teknologi Fakultas Teknik, 2010)
Abstract The success of agricultural development cannot be separated from the development of technology. Rapid development of the agricultural sector is started from the green revolution, as the impact of population explosion, causes a worry of food shortages. The green revolution encourages the discovery of new tools and methods that can increase agricultural production especially food. Starting from the development of seed technology, that high-productivity and short-aged seeds found, until other technologies created. The technology of agricultural machinery begins to develop along with the requirement of tools that can quickly and efficiently assist laborâs work. This study aims at: 1) recognizing the development of rice production growth in central Java, 2) understanding the need of food, especially rice in Central Java, 3) the role of agricultural machinery in increasing rice production in Central Java, and 4) barriers and challenges in developing the agricultural machine tool. The method used in research is descriptive analysis method, that is the writing of actual problem solving, then the data are collected, compiled, described and analyzed (Suracmad, 1980). Discussion on the problems by using literatures and secondary data as information sources, then analyze the data to be interpreted. The problem can be solved through these data sources and reviewing literature until finding the solution. The result of research proves that the growth of rice production in Central Java is smaller than the population growth. Year by year, the use of agricultural machinery has developed. Agricultural machinery can increase rice production in Central Java. The production can be increased through the efficiency of farm management. Therefore, it can change the crop patterns. The use of agricultural machinery also can increase farmer productivities and save labors. However, agricultural machinery has problems of the application due to various technical, operations, social, cultural, and economic. Keywords: Agricultural machine tools, Production, Rice.